THE ANALYSIS AND THE TRENDS OF ELECTROCLEANERS DEVELOPMENT - Garazha, V.V.; Davidenko, Y.P.; Hung, Dinh Tan (Proceedings of National Aviation University (archive), 2005)
On the basis of the analysis of practical use of electrocleaners the urgency of development of their classification is necessary. As an Low-concentrated diluted emulsions and suspensions destruction, using for offered classification, the decision methods of the multipurpose complex problems directed in the search of the effective technologies of electrotreatment for providing working liquids cleanliness of aircraft functional systems have been forecasted.